5G verticals : customizing applications, technologies and deployment techniques - Vannithamby, Rath; Soong, Anthony C. K. (IEEE series, 2020)
"This book brings together a group of visionaries and technical experts from academia to industry to discuss the usages and technologies that will comprise the next wave of cellular advancements and services, referred to as 5G Verticals. Earlier network generations (2G to 4G) have been designed as general purpose connectivity platforms with limited differentiation capabilities across use cases; a one size fit all approach. 5G networks, however, are going to be different. It will usher in the era of on demand customizable mobile network. This will create an ecosystem for technical and business innovation involving vertical markets such as automotive, healthcare, manufacturing, energy, food and agriculture, city management, government, public transportation, Media & Entertainment, etc. It will serve a larger portfolio of applications with various requirements ranging from high reliability to ultra-low latency going through high bandwidth and mobility. In this book, we will cover how 5G will enable a customized experience. In particular, we explore a) applications and usages of various 5G verticals, b) a set of key metrics for these usages and their corresponding target requirements, and c) potential network architectures and enabling technologies to meet the requirements of 5G verticals"--